Kekosongan Hukum Batas Waktu Pengisian Jabatan Wakil Kepala Daerah Kabupaten Ciamis Pasca Pemilihan Kepala Daerah Tahun 2024 - Aan Afandi; Dykasakti Azhar Nytotama (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the legal framework governing the appointment of deputy regional heads in Indonesia, examine the implications of the normative vacuum regarding the time limit for filling the vacancy of the Deputy Regent of Ciamis following the 2024 Regional Head Election (Pilkada) on legal certainty and the balance of power in regional governance, and formulate an ideal regulatory model for establishing a definite time limit for such appointments. This research employs a normative legal research method using statutory, conceptual, and case approaches. Legal materials were analyzed through relevant legislation concerning regional government and regional head elections, supported by the theories of the rule of law, legal certainty, checks and balances, and legal vacuum. The findings indicate that existing legislation regulates the procedural mechanism for filling vacancies in the office of deputy regional heads but does not prescribe a specific time limit for candidate nomination, election by the Regional House of Representatives (DPRD), or appointment by the central government. This normative gap creates legal uncertainty and may lead to the concentration of executive power while weakening checks and balances in regional governance. Therefore, this study proposes a legal reconstruction by introducing clear and measurable time limits to ensure legal certainty and effective regional governance. .